Prediksi Financial Distress dan Pengaruhnya Terhadap Return Saham Perusahaan Sub Sektor Industri Tektil dan Garmen yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021 - Hertina, Dede; Tsaniya, Fatharani Nur (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The aim of this research is to find out the potential for financial difficulties in the textile and garment industry subsectors for the 2017–2021 period. The research population consisted of 21 companies, with a research sample of as many as 10 companies. As for techniques in data analysis, it begins by measuring the potential for financial difficulties through the Springate calculation equation model, followed by panel regression data analysis, the classic assumption test, determination (R2), and hypothesis testing. According to research, eight of the ten companies that comprised the research sample declared financial difficulties during the study period. While the hypothesis test results show that working capital contributes to total assets, earnings before interest and tax contribute to total assets, profit before tax aids in the smooth discharge of liabilities, and sales of total assets have no significant impact on the company's stock return.